2021
DOI: 10.1038/s41598-021-82990-y
|View full text |Cite
|
Sign up to set email alerts
|

BKM120 sensitizes BRCA-proficient triple negative breast cancer cells to olaparib through regulating FOXM1 and Exo1 expression

Abstract: Poly (ADP-ribose) polymerase (PARP) inhibitors offer a significant clinical benefit for triple-negative breast cancers (TNBCs) with BRCA1/2 mutation. However, the narrow clinical indication limits the development of PARP inhibitors. Phosphoinositide 3-kinase (PI3K) inhibition sensitizes BRCA-proficient TNBC to PARP inhibition, which broadens the indication of PARP inhibitors. Previously researches have reported that PI3K inhibition induced the defect of homologous recombination (HR) mediated repair by downregu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 46 publications
2
24
0
Order By: Relevance
“…Exonuclease 1 (EXO1) is associated with increased levels of genomic instability in the telomere region, and this widespread genomic instability can promote cancer progression [43]. EXO1 is a therapeutic target of TNBC that serves an important role in the DDR by inhibiting the activity of PARP [44,45]. In our study, we found that the EXO1 gene has a positive correlation with eosinophils.…”
Section: Discussionmentioning
confidence: 62%
“…Exonuclease 1 (EXO1) is associated with increased levels of genomic instability in the telomere region, and this widespread genomic instability can promote cancer progression [43]. EXO1 is a therapeutic target of TNBC that serves an important role in the DDR by inhibiting the activity of PARP [44,45]. In our study, we found that the EXO1 gene has a positive correlation with eosinophils.…”
Section: Discussionmentioning
confidence: 62%
“…Exonuclease 1 (EXO1) is associated with increased levels of genomic instability in the telomere region, and this widespread genomic instability can promote cancer progression ( Maciejowski and de Lange, 2017 ). EXO1 is a therapeutic target of TNBC that serves an important role in the DDR by inhibiting the activity of PARP ( Quist et al, 2019 ; Li et al, 2021 ). In our study, we found that the EXO1 gene has a positive correlation with eosinophils.…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that EXO1 and EME2 are correlated with homologous recombination repair pathway in the functional annotation based on the Reactome database ( Figure 2 b). Several studies have reported that olaparib can inhibit the activity of EXO1 protein leading to inactivation of PARP enzymes [ 67 , 68 , 69 ], whereas there is currently no study that reports the direct interaction between PARP inhibitors and EME2 .…”
Section: Discussionmentioning
confidence: 99%